A review of the new GLP-1 receptor agonist/basal insulin fixed-ratio combination products. (March 2018) - Nuffer, Wesley; Guesnier, Ashley; Trujillo, Jennifer M.
There have been several new treatment approaches established for the management of hyperglycemia in type 2 diabetes (T2D), with treatment guidelines listing both glucagon-like peptide 1 receptor agonists (GLP-1 RAs) and basal insulin therapies as considerations for patients who have failed to control their blood glucose with oral antidiabetic agents. New studies have highlighted the importance of initiating combination therapy earlier in the T2D disease process to avoid clinical inertia and prevent the long-term complications arising from uncontrolled diabetes. Until recently, both GLP-1 RAs and basal insulin therapies were only available as single agents, but there are now two combination pen devices that deliver both a GLP-1 RA and basal insulin simultaneously. This article reviews the current clinical evidence evaluating the use of these combination GLP-1 RA/basal insulin preparations to treat T2D, presents both potential benefits as well as possible downsides with the use of these agents, and discusses the current place in therapy these products represent in the management of T2D.